-Relatives' Experiences When a Family Member Is Confirmed Brain Dead and Becomes a Potential Organ Donor-A Literature Review - Birgitta Kerstis RN, PhD; Margareta Widarsson RN, RM, PhD (SAGE Publishing, 2020)
Introduction Most healthcare professionals rarely experience situations of a request for organ donation being made to the patient's family and need to have knowledge and understanding of the relatives' experiences. Objective To describe relatives' experiences when a family member is confirmed brain dead and becomes a potential organ donor. Methods A literature review and a thematic data analysis were undertaken, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting process. A total of 18 papers, 15 qualitative and 3 quantitative, published from 2010 to 2019, were included. The electronic search was carried out in January 2019. Results The overarching theme When life ceases emerged as a description of relatives' experiences during the donation process, including five subthemes: cognitive dissonance and becoming overwhelmed with emotions, interacting with healthcare professionals, being in a complex decision-making process, the need for proximity and privacy, and feeling hope for the future. The relatives had different needs during the donation process. They were often in shock when the declaration of brain death was presented, and the donation request was made, which affected their ability to assimilate and understand information. They had difficulty understanding the concept of brain death. The healthcare professionals caring for the patient had an impact on how the relatives felt after the donation process. Furthermore, relatives needed follow-up to process their loss. Conclusion Caring science with an explicit relative perspective during the donor process is limited. The grief process is individual for every relative, as the donation process affects relatives' processing of their loss. We assert that intensive care unit nurses should be included when essential information is given, as they often work closest to the patient and her or his family. Furthermore, the relatives need to be followed up afterwards, in order to have questions answered and to process the grief, together with healthcare professionals who have insight into the hospital stay and the donation process.